Penyuluhan Peranan Perbankan dan Lembaga Keuangan Lainnya bagi Siswa SMA Negeri 3 Prabumulih Sumatera Selatan - Emma Lilianti; Reva Maria Valianti; Juni Darwin; Hendri Saladin (IKIP PGRI Bojonegoro, 2019)
ABSTRACTBanks are institutions that have an intermediary role or as intermediaries between excess funds (surplus spending units) and those who are underfunded (defending spending units) that indirectly help circulate money in society. In order to remain able to carry out its role, it requires public trust in the performance of the bank. Purposes of Counseling 1) The introduction of early banking among students so that students can help the government increase the level of financial literacy, 2) prevent students from making waste and get caught up in the negative impact of technological developments in the form of online gambling and online games that suck students' time, funds and concentration in learning . 3) To improve students' insight and make a strong and competent person. PKM with counseling methods targeting 50th and 11th grade students of Prabumulih State Senior High School numbered 50 people. Outreach results show that 87% of students understand banking from the questions given at the end of the activity. With the introduction of banking, it was able to change the mindset of the consumptive students to become entrepreneurs who were able to manage money and like business. Another outcome of this counseling is that students finally have a personal account that is accommodated by bank officials who participate in the extension activities. Extension material is summarized and made a module about banking for student and student learning materials.Keywords: Banking role, Financial institution, Senior high school 3 PrabumulihABSTRAKBank adalah Lembaga yang memiliki peran intermediasi atau sebagai perantara antara pihak yang kelebihan dana (surplus spending unit) dengan pihak yang kekurangan dana (defisist spendingunit) yang secara tidak langsung membantu perputaran uang dalam masyarakat. Agar tetap mampu menjalankan perannya tersebut dibutuhkan kepercayaan masyarakat terhadap kinerja bank. Tujuan Penyuluhan 1) Pengenalan perbankan sejak dini di kalangan pelajar agar pelajar dapat membantu pemerintah meningkatkan tingkat literasi keuangan, 2) Â mencegah para pelajar melakukan pemborosan dan terjebak dampak negatif perkembangan teknologi berupa game online dan perjudian online yang menyedot waktu, dana dan konsentrasi siswa dalam belajar. 3) Untuk meningkatkan Â wawasan siswa dan menjadikan pribadi yang tangguh dan mampu bersaing. PKM dengan metode penyuluhan dengan sasaran siswa kelas XI dan XII SMA Negeri 3 Prabumulih berjumlah 50 orang. Hasil penyuluhan menunjukkan bahwa 87% siswa paham tentang perbankan dari pertanyaan yang diberikan di sesi akhir kegiatan. Dengan pengenalan perbankan mampu merubah mindset kalangan pelajar konsuntif menjadi entrepreunership yang mampu mengelola uang dan menyukai bisnis. Luaran lain dari penyuluhan ini siswa akhirnya memiliki rekening pribadi yang diakomodir pembuatan oleh petugas bank yang ikut serta dalam kegiatan penyuluhan tersebut. Materi penyuluhan dirangkum dan dijadikan modul tentang perbankan untuk materi belajar siswa dan mahasiswa.Kata kunci: Peranan perbankan, Lembaga keuangan, SMA Negeri 3 Prabumulih